Emotional Experiences Drive Customer Loyalty in Indonesia : Pengalaman Emosional Mendorong Loyalitas Pelanggan di Indonesia - Gideon Carakaardi Wicaksana; Elia Ardyan (Academia Open, 2024)
General Background: Customer loyalty has evolved significantly with the rise of technology and social media, where emotional experiences now play a crucial role. Specific Background: This study focuses on Taman Dayu, a resort villa in Pasuruan, East Java, known for its natural scenery and ambience. Knowledge Gap: There is limited research on how emotional experiences and service quality influence consumer loyalty in the property sector, particularly in the context of Taman Dayu. Aims: This research aims to analyze how consumers form emotional bonds with brands and properties and examine the role of service quality in strengthening these relationships. Method: The study used a quantitative approach with a sample of 106 respondents from 250 distributed questionnaires, processed using SPSS. The research involved creating a questionnaire that adapted operational items from previous studies. Emotional experience, customer loyalty, and service quality were the key variables examined. A simple moderation regression method was employed to determine if the relationship between emotional experience and customer loyalty is moderated by service quality. Results: The findings indicate that emotional experiences significantly impact consumer loyalty. Positive emotions such as happiness and satisfaction lead to higher loyalty levels, characterized by repeat purchases and recommendations. Although service quality did not significantly moderate the relationship between emotions and loyalty, it was found to enhance positive emotional experiences, underscoring its importance in fostering consumer loyalty. Novelty: This research highlights the significant impact of emotional experiences on consumer loyalty in the property industry, a relatively underexplored area, especially for a specific location like Taman Dayu. Implications: The study suggests that property managers should focus on enhancing emotional experiences and maintaining high service quality to build and strengthen emotional bonds with consumers, ultimately increasing loyalty. Future research should consider larger, more diverse samples and explore additional variables such as pricing and secondary market dynamics to provide a more comprehensive understanding of consumer loyalty. Highlight: Positive emotions significantly boost customer loyalty. Service quality enhances emotions but doesn't moderate loyalty. Future research should use diverse samples and explore pricing and promotions. Keyword: Customer loyalty, emotional experience, service quality, Taman Dayu, quantitative research